Integration of inventive problem solving in project-based learning for building construction program through module development - Michael, Karen Sharmini; Yee, Mei Heong; Tee, Tze Kiong; Kok, Boon Ching; Azid, Nurulwahida; Nur Rahma Putra, Andika Bagus; Salim, Mohd Azli; Marniati, Marniati (2021)
. Cooperative learning and hands-on techniques are important dimensions for Building Construction students to build skills and gain knowledge. Therefore, the appropriate approach that needs to be given to Building Construction students is Project-Based Learning (PBL). PBL is meaningful question-based learning, encourages Building Construction students to think deeply and increase their curiosity. The problems that need to be solved are close to the real-world context. Accordingly, to increase students' knowledge to think more creatively and innovatively, a theory can help Building Construction students solve problems that is the Theory of Inventive Problem Solving (TRIZ) has been integrated into PBL. This study aims to develop the TRIZ Integration module in PBL by analyzing the format appropriateness feedback, content, and usability of the module from lecturers and students. This study uses a quantitative approach involving five lecturers and 30 students from the field of Building Construction. Data were analyzed descriptively and presented in terms of frequency and percentage. The study's findings show that 100% of Building Construction lecturers, and students agree with this module format's suitability. Besides, 97.3% of lecturers and 100% of students also agreed with the suitability of the content of this module developed. As for the module's usability, 90% of lecturers and 100% of students agree that Building Construction students can use this developed module. In conclusion, this module successfully helps Building Construction lecturers and students solve inventive problems in PBL effectively